The Effectiveness of a Proposed Counseling Program Based on Dialectical Behavior Therapy for Middle School Students. (Journal of the College of Basic Education, 2025)
The current research aims to identify the effectiveness of a proposed counseling program based on Dialectical Behavior Therapy (DBT) among middle school students. To achieve the research objective, the researchers developed a scale for unplanned impulsive behavior, consisting of 30 items distributed across three domains. The psychometric properties of the scale were established through validity and reliability testing. Additionally, a DBT-based counseling program was designed, comprising 12 sessions at a rate of two sessions per week. The researchers adopted a quasi-experimental method, with an experimental sample size of 20 students. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS). The results indicated that the program was effective in reducing unplanned impulsive behavior among middle school students. The researchers concluded with a set of recommendations and suggestions.